Índice de inclusión en una Institución Educativa de la ciudad de Cúcuta. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: The inclusion index is a tool that allows educational institutions to revise their insti-tutional practices in the light of inclusive criteria. The objective of the study is to recognize the current state of attention to diversity, analyze strengths and opportunities for improvement. METHODS: The investigation is of type quantitative, with descriptive character of transverse court, under the Perspec-tive of Laws and the Differential Approach. RESULTS: From the averages obtained of four areas of management, the total of the global institutional index corresponds to 3.43. ANALYSIS AND DIS-CUSSION: The interpretation of the Index in this range indicates that in the Educational Institution, the inclusion process is developed and evaluated continuously; however, there are processes below the average, which must be improved in order to provide an inclusive education. CONCLUSIONS:On the general level, in the Educational Institution, inside the four management areas were obtained positive values that indicate that the efforts and inclusive actions are routed at the search for true in-clusion.
Keywords: differential approach; education; inclusión; managemen